The 2024 international survey of platelet products and practice - Ohto, Hitoshi; Flegel, Willy A.; van der Meer, Pieter F.; Ngoma, Alain M.; Nollet, Kenneth E.; Choudhury, Nabajyoti; Legler, Tobias J.; Tani, Yoshihiko; Kwon, So-Yong; Chiueh, Tzong-Shi; Sarantuya, Badmaarag Ruby; Kam, Wooi Seong; et al. (Transfusion and apheresis science, 2025)
Previously, two international surveys have addressed the wider application of platelet collection by apheresis technology and practical issues of platelet transfusion. A questionnaire was sent to persons with leadership roles related to blood banking and transfusion medicine in their countries/areas/centers, to document the implementation of modern technologies for platelet manufacturing, preservation, and transfusion risk reduction. Responses to the questionnaire finally came from 52 contributors in 40 countries/areas. Adult platelet doses ranged between 2.0×1011 and 3.0×1011 (median 2.5×1011). In approximately 10 % of centers, apheresis platelets comprised more than 90 % of the platelet inventory. More than 70 % of centers adopted universal or near universal leukocyte-reduction by filtration, apheresis, or both. Almost 20 % of centers irradiated all platelet products. Cold-stored platelets were rarely reported; only 3 centers produce such components for 1 % to 5 % of their supply. The use of platelet additive solution was reported by 18 responders (45 %), mainly in Europe, USA, and Australasia. Bacterial detection systems were reported by 18 responders from around the globe. One fatality was reported after transfusion of a platelet product contaminated with Bacillus cereus, whereas no sequelae were observed after transfusion of >350 platelet products contaminated by Cutibacteriae. Pathogen-reduction/pathogen-inactivation technology has been adopted in 15 centers, with little or no extended expiration period. Export of platelets across national borders was extremely rare. With this addition to the literature on platelet transfusion, considerable heterogeneity in collection, processing, and transfusion can be seen across the globe, through which readers may adopt, and adapt, best practices for their unique local circumstances.